KUALITAS SPERMATOZOA TIKUS PUTIH ( KUALITAS SPERMATOZOA TIKUS PUTIH ( KUALITAS SPERMATOZOA TIKUS PUTIH ( KUALITAS SPERMATOZOA TIKUS PUTIH ( R a tt u s n o r v e g i c u s R a tt u s n o r v e g i c u s R a tt u s n o r v e g i c u s R a tt u s n o r v e g i c u s L) S L) S L) S L) SETELAH ETELAH ETELAH ETELAH PERLAKUAN DENGAN BORAKS - Kspul Kaspul (Universitas Lambung Mangkurat, 2004)
The objective of this research is to assess the effects of sodium borat on concentration, motility, velocity of movement, and normal morphology of spermatozoa in rats. Fifty male rats at four months age were fed in five trearment groups per day, i. e : (1) without treatment, (2) placebo of sodium borate ; 1 ml CMC 1%, (3) 200 mg sodium borate per kg body weight, (4) 400 mg sodium borate per kg body weight, and (5) 600 mg sodium borate per kg body weight. The concentration, motility velocity of movement and normal morphology of spermatozoa were research with modification of First method (1991) ; Suhadi and Arsyad method (1983). The result of this research showed that sodium borat decreased concentration, motility, velocity of movement and normal morphology of spermatozoa in rats.